2009
DOI: 10.1016/j.jtcvs.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Ministernotomy versus conventional sternotomy for aortic valve replacement: A systematic review and meta-analysis

Abstract: Ministernotomy can be performed safely for aortic valve replacement, without increased risk of death or other major complication; however, few objective advantages have been shown. Surgeons must conduct well-designed, prospective studies of relevant, consistent clinical outcomes to determine the role of ministernotomy in cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
273
3
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(311 citation statements)
references
References 34 publications
25
273
3
10
Order By: Relevance
“…Ding et al (2012) evaluated ALMT in congenital heart disease and suggested that this had a longer CPB time and ACCT, but shorter intubation time, ICU time, and LOHS. The remaining three studies compared a minimally invasive procedure with conventional sternotomy for aortic valve replacement (Murtuza et al, 2008;Brown et al, 2009;Khoshbin et al, 2011) and included RCTs and non-randomized studies. They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al (2012) evaluated ALMT in congenital heart disease and suggested that this had a longer CPB time and ACCT, but shorter intubation time, ICU time, and LOHS. The remaining three studies compared a minimally invasive procedure with conventional sternotomy for aortic valve replacement (Murtuza et al, 2008;Brown et al, 2009;Khoshbin et al, 2011) and included RCTs and non-randomized studies. They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three studies compared a minimally invasive procedure with conventional sternotomy for aortic valve replacement (Murtuza et al, 2008;Brown et al, 2009;Khoshbin et al, 2011) and included RCTs and non-randomized studies. They concluded that a mini-sternotomy can be performed safely for aortic valve replacement without an increased risk of death, major complications (Khoshbin et al, 2011), a reduction in ICU stay time (Brown et al, 2009), or clinical benefit (Aybek et al, 2000). Moreover, we excluded 12 studies because they had no control groups (Loulmet et al, 1998;Mishra et al, 1999;Riess et al, 2001;Grossi et al, 2002;Onnasch et al, 2002b;Aybek et al, 2006;Martin et al, 2006;Seeburger et al, 2008;Glaubera et al, 2009;Müller et al, 2011;Reser et al, 2012), which ranged from 22 to 1339 in sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The TAVI technology has been adopted in sutureless valves, which can be deployed under direct vision via conventional or minimally invasive approaches without the need of a catheter. Minimally invasive AVR (MAVR) has demonstrated similar results to conventional AVR in regards to clinical outcomes, with the added benefit of improved patient satisfaction (6).…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the incision from an average of 24.5 to 7.17 cm with a ministernotomy, or a 5 cm incision with a thoracotomy (13,14). MiniAVR has been shown to: reduce length of intensive care unit (ICU) and hospital stay, reduce ventilation time, decrease the need for blood transfusion, decrease pain, and improve the cosmetic result (15)(16)(17). A Cochrane review that included seven randomized controlled trials compared AVR via median sternotomy vs. were comparable between the minithoracotomy and ministernotomy groups, respectively (20).…”
Section: Miniavrmentioning
confidence: 99%